2021
DOI: 10.36260/rbr.v10i8.1384
|View full text |Cite
|
Sign up to set email alerts
|

Conocimiento didáctico del contenido. Una revisión sistemática exploratoria

Abstract: El presente estudio gira entorno a la determinación de las principales tendencias en la producción científica frente al conocimiento didáctico del contenido (CDC). Para dicha tarea se hizo uso de la investigación cualitativa en específico de la revisión sistemática exploratoria, lo que muestra quien, que, donde y como se ha hecho o abordado un tema en especial. Se revisaron investigaciones publicadas en bases de datos científicas en idioma español entre los años 2015 y 2021, las cuales se registraron en resúme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The PCK is likely to be approached and worked on in any discipline or science that needs to establish how effectively what should be taught reaches the students (Montoya Grisales & Arroyave Giraldo, 2021), studies have been found on university teaching (Díaz Pacheco, 2017;Medina et al, 2016;Mentado Labao et al, 2017;Parga-Lozano & Moreno-Torres, 2017); physics (Brines Brines et al, 2016;Campo Nava & Ramírez Díaz, 2019;Melo et al, 2017Melo et al, , 2020, biology (González & Rossi, 2015;Ravanal Moreno & López-Cortés, 2016), among others. A matter that from the didactic aspect puts the reflective action of the teacher to the test based on the contents of a personal order, theoretical or practical required by PE students (Montoya-Grisales et al, 2022), in the field of the PCK has been conceptualized as:…”
Section: Introductionmentioning
confidence: 99%
“…The PCK is likely to be approached and worked on in any discipline or science that needs to establish how effectively what should be taught reaches the students (Montoya Grisales & Arroyave Giraldo, 2021), studies have been found on university teaching (Díaz Pacheco, 2017;Medina et al, 2016;Mentado Labao et al, 2017;Parga-Lozano & Moreno-Torres, 2017); physics (Brines Brines et al, 2016;Campo Nava & Ramírez Díaz, 2019;Melo et al, 2017Melo et al, , 2020, biology (González & Rossi, 2015;Ravanal Moreno & López-Cortés, 2016), among others. A matter that from the didactic aspect puts the reflective action of the teacher to the test based on the contents of a personal order, theoretical or practical required by PE students (Montoya-Grisales et al, 2022), in the field of the PCK has been conceptualized as:…”
Section: Introductionmentioning
confidence: 99%